Предмет: Математика,
автор: plshelp4
Решите ПЖ
![6(7x - 11) - 13(x - 6) = 14(2x + 1) 6(7x - 11) - 13(x - 6) = 14(2x + 1)](https://tex.z-dn.net/?f=6%287x+-+11%29+-+13%28x+-+6%29+%3D+14%282x+%2B+1%29)
Ответы
Автор ответа:
2
42x-66-13x+78=28x+14
42x-13x-28x=14-78+66
x=2
42x-13x-28x=14-78+66
x=2
Автор ответа:
2
Ответ: 2.
Похожие вопросы
Предмет: Русский язык,
автор: farhatdvumat
Предмет: Геометрия,
автор: PESHIMATEMPLS
Предмет: География,
автор: pavelberdnikov5404
Предмет: Литература,
автор: olgaizg
Предмет: История,
автор: OneHeep